Molecular cloning and characterization of the cDNA coding for the biotin-containing subunit of the chloroplastic acetyl-coenzyme A carboxylase. - Choi, J K (1995)
We report the molecular cloning and sequence of the cDNA coding for the biotin-containing subunit of the chloroplastic acetylcoenzyme A (CoA) carboxylase (ACCase) of Arabidopsis thaliana (CAC1). The 3' end of the CAC1 sequence, coding for a peptide of 94 amino acids, which includes a putative biotinylation motif, was expressed in Escherichia coli as a glutathione-S-transferase (GST) fusion protein. The resulting GST-CAC1 fusion protein was biotinylated in vivo, indicating that CAC1 codes for a biotin-containing protein. Antibodies generated to the GST-CAC1 protein reacted solely with the 38-kD biotin-containing polypeptide of Arabidopsis. Furthermore, these antibodies inhibited ACCase activity in extracts from Arabidopsis leaves. The deduced amino acid sequence of CAC1 has an apparent N-terminal chloroplast-targeting transit peptide. The CAC1 protein is coded by a single Arabidopsis gene, and its mRNA accumulates to the highest levels in organs that are undergoing rapid growth. The amino acid sequence of the CAC1 protein is most similar to the biotin carboxyl-carrier protein component of eubacterial ACCases. These characterizations identify CAC1 as the biotin-containing subunit of the plastidic, heteromeric ACCase of Arabidopsis. The results support the ancient origin of the two structurally distinct ACCases of plants.